Relocation Policy of Street Vendors in Malioboro: Review of Policy Formulation Analysis Study (Agile Governance and Innovation Measurement Journal, 2024)
In public policy formulation, the interests and welfare of the community must be prioritized as the direction for policy formulators. Policy formulation is oriented towards the needs, desires, and interests of the community so that later it will receive full support from the community. Policy formulation is also a very important stage and must be carried out appropriately and comprehensively. The stages in the policy formulation process are problem identification, agenda setting, policy problem formulation, and policy design (Alaslan, 2021). In the process of policy formulation for the relocation of Malioboro street vendors, problem identification is first carried out to identify existing problems based on the infrastructure aspects of facilities and infrastructure such as the loss of pedestrian rights due to street vendors selling on the sidewalk. The policy formulation by the government can finally be realized little by little. The relocation policy of Malioboro street vendors affects tourist visits, which indirectly affects the street vendors. With the relocation of street vendors, they get adequate public facilities, ease of mobility for traders, security guarantees, and time efficiency.